Answer:
![\begin{gathered} \text{First number=16} \\ \text{second number=22} \\ \text{Third number=66} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kdsy71d2sghtsvtjh6t3bqpqerdc0ers20.png)
Step-by-step explanation:
Let the unknown numbers be x, y, and z where
• First number = x
,
• Second number = y
,
• Third number = z
If the sum of the three numbers is 104, then;
![x+y+z=104](https://img.qammunity.org/2023/formulas/mathematics/college/ou3x9w6n81tbbaw1zgxbsc3xdml71onl9u.png)
If the first number is 6 less than the second, hence;
![\begin{gathered} x=y-6 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4g5bxfb8t3tyjb4n042b5dq1jzee59l67k.png)
Also, if the third number is 3 times the second, then;
![z=3y](https://img.qammunity.org/2023/formulas/mathematics/college/k44yqa8b9h1g77he7k8lzfh8utgo41ajzs.png)
Substitute equations 2 and 3 into equation 1 to reduce the variables to the function of "y" only:
![\begin{gathered} x+y+z=104 \\ (y-6)+y+3y=104 \\ y-6+4y=104 \\ 5y-6=104 \\ 5y=104+6 \\ 5y=110\rbrack \\ y=(110)/(5) \\ y=22 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/el2ov5x39jggvzuvtbdaf7nz23dmh4qtit.png)
Get the first number "x"
![\begin{gathered} x=y-6 \\ x=22-6 \\ x=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kaejp8h9b1t2pn70qix1mai87awb99uack.png)
Get the third number "z"
![\begin{gathered} z=3y \\ z=3(22) \\ z=66 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tevncxfdp4b7hgql5u2dxhg9toqxqq3hvh.png)
Therefore the three numbers are 16, 22, and 66.